2017
DOI: 10.1159/000454840
|View full text |Cite
|
Sign up to set email alerts
|

Posterior versus Anterior Circulation Stroke in Young Adults: A Comparative Study of Stroke Aetiologies and Risk Factors in Stroke among Young Fabry Patients (sifap1)

Abstract: Background: Although 20-30% of all strokes occur in the posterior circulation, few studies have explored the characteristics of patients with strokes in the posterior compared to the anterior circulation so far. Especially data on young patients is missing. Methods: In this secondary analysis of data of the prospective multi-centre European sifap1 study that investigated stroke and transient ischemic attack (TIA) patients aged 18-55 years, we compared vascular risk factors, stroke aetiology, presence of white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
6
27
1
1
Order By: Relevance
“…This vulnerability of these regions may be related to the relatively poor blood supply of the anterior circulation. A recent study in young adults reported that large-artery atherosclerosis was more frequent in patients with anterior circulation stroke than in those with posterior circulation stroke ( 32 ), which was partly consistent with our result. Moreover, juxtacortical white matter, consists of U-fibers instead of long white matter tracts, is mostly supplied by short vessels at the boundary of white matter and cortex or the end of long penetrating medullary vessels, which would be easily influenced by atherosclerosis ( 3 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…This vulnerability of these regions may be related to the relatively poor blood supply of the anterior circulation. A recent study in young adults reported that large-artery atherosclerosis was more frequent in patients with anterior circulation stroke than in those with posterior circulation stroke ( 32 ), which was partly consistent with our result. Moreover, juxtacortical white matter, consists of U-fibers instead of long white matter tracts, is mostly supplied by short vessels at the boundary of white matter and cortex or the end of long penetrating medullary vessels, which would be easily influenced by atherosclerosis ( 3 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…The patients with acute medullary infarction were later confirmed as having vertebral artery dissection. In fact, vertebral artery dissection has been recognized as a frequent cause of posterior circulation stroke among young adults [ 13 , 24 ]. The PC-ASPECTS cannot be accurately assessed in medullary infarction.…”
Section: Discussionmentioning
confidence: 99%
“…However, male sex as risk factor for PCiS vs. ACiS has been reported previously [19][20][21]. A male preponderance in PCiS has been observed in both children [30] and young adults [5]. There are studies indicating sex differences in the autoregulatory capacity of the basilar artery in young teens [31] and a significantly lower cerebrovascular reactivity to l-arginine in the posterior circulation in adult males [32].…”
Section: Specific Risk Factors In Pcismentioning
confidence: 90%
“…To a large extent, PCiS and anterior circulation ischemic stroke (ACiS) share vascular risk factors and stroke mechanisms [1,4]. PCiS has been reported to occur more commonly than ACiS in young patients in whom cervical artery dissection is more frequent [5] and in patients with MELAS and Fabry's disease [6]. Previous studies comparing PCiS and ACiS suffer from heterogeneous sample sizes, diagnostic criteria, imaging methods, and subtype classification.…”
Section: Introductionmentioning
confidence: 99%